2010
DOI: 10.1002/da.20700
|View full text |Cite
|
Sign up to set email alerts
|

Trichotillomania (hair pulling disorder), skin picking disorder, and stereotypic movement disorder: toward DSM-V

Abstract: In DSM-IV-TR, trichotillomania (TTM) is classified as an impulse control disorder (not classified elsewhere), skin picking lacks its own diagnostic category (but might be diagnosed as an impulse control disorder not otherwise specified), and stereotypic movement disorder is classified as a disorder usually first diagnosed in infancy, childhood, or adolescence. ICD-10 classifies TTM as a habit and impulse disorder, and includes stereotyped movement disorders in a section on other behavioral and emotional disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 137 publications
(167 reference statements)
6
133
0
14
Order By: Relevance
“…7,8 Some authors have suggested that SMD should be a single entity, which includes both stereotypic behaviors in those with intellectual disability (e.g., head-banging) and body-focused repetitive behaviors (e.g., hair-pulling, skinpicking, cheek-chewing, lip-biting) in those without intellectual disability, and that this broader construct should be included in the chapter on OCRD, alongside tic disorders. 9 This view is consistent with the hypothesis that stereotypies in a range of disorders have overlaps in underlying psychobiology. 10,11 According to this line of thinking, stereotypies such as head-banging and cheekchewing 12 could then be classified alongside trichotillomania and skin-picking disorder.…”
Section: ) In Which Grouping Should Smd Be Classified?supporting
confidence: 86%
“…7,8 Some authors have suggested that SMD should be a single entity, which includes both stereotypic behaviors in those with intellectual disability (e.g., head-banging) and body-focused repetitive behaviors (e.g., hair-pulling, skinpicking, cheek-chewing, lip-biting) in those without intellectual disability, and that this broader construct should be included in the chapter on OCRD, alongside tic disorders. 9 This view is consistent with the hypothesis that stereotypies in a range of disorders have overlaps in underlying psychobiology. 10,11 According to this line of thinking, stereotypies such as head-banging and cheekchewing 12 could then be classified alongside trichotillomania and skin-picking disorder.…”
Section: ) In Which Grouping Should Smd Be Classified?supporting
confidence: 86%
“…On the other hand, skin-picking disorder differs from OCD in terms of clinical presentation (e.g., less likely to have obsessive thoughts), neurocognition (e.g., tends to be more impulsive), and in terms of treatment approaches (e.g., serotonin reuptake inhibitors may be less effective). 23,30 A final concern is about the clinical utility of the ICD-10 descriptions of skin-picking disorder. Field trials for the DSM-5 criteria found that most clinicians felt the criteria were helpful and easy to implement.…”
Section: Skin-picking Disordermentioning
confidence: 99%
“…Eğer ayrı bir bozukluk olarak tanımlanırsa tırnak yeme, dudak çiğneme, burun yolma gibi diğer alışkanlıkların da sınıflandırma sistemlerine girmesinin yolunun açılacağı ifade edilmiş-tir. [78] Ancak, deri yolma bozukluğunun literatürde çok uzun yıllardır tanımlanan, tanısal ölçütler önerilen bir sendrom olması, bazı olgularda önemli tıbbi sonuçlar doğurabilmesi, beklenebilir bir yanıt olduğuna ilişkin kanıt olmamakla birlikte belirli negatif etkilerle alevlenebilmesi, [1] çok yeterli olmasa da deri yolmanın nörobiyolojisine ilişkin bazı verilerin bulunması [16,18,32] birincil olarak sosyal çatışmaların sonucunda ortaya çıkmaması, daha fazla çalışmaya gereksinim olmakla birlikte klinik seyir, ektanı ve tedaviye yanıt alanlarında deri yolma bozukluğunun tanısal geçerliliğini destekleyen verilerin bulunması DSM-5'de ayrı bir tanı kategorisi olmasının gerekçeleri olarak öne sürülmüştür. [78] Deri yolma bozukluğunun ayrı bir tanı kategorisi olması, bu durumla ilgili farkında-lığı arttıracak, hastaların uygun değerlendirme ve tedavisini sağlayacak, bu alandaki araştırmalara ivme kazandıracaktır.…”
Section: Tanı öLçütleriunclassified
“…[78] Ancak, deri yolma bozukluğunun literatürde çok uzun yıllardır tanımlanan, tanısal ölçütler önerilen bir sendrom olması, bazı olgularda önemli tıbbi sonuçlar doğurabilmesi, beklenebilir bir yanıt olduğuna ilişkin kanıt olmamakla birlikte belirli negatif etkilerle alevlenebilmesi, [1] çok yeterli olmasa da deri yolmanın nörobiyolojisine ilişkin bazı verilerin bulunması [16,18,32] birincil olarak sosyal çatışmaların sonucunda ortaya çıkmaması, daha fazla çalışmaya gereksinim olmakla birlikte klinik seyir, ektanı ve tedaviye yanıt alanlarında deri yolma bozukluğunun tanısal geçerliliğini destekleyen verilerin bulunması DSM-5'de ayrı bir tanı kategorisi olmasının gerekçeleri olarak öne sürülmüştür. [78] Deri yolma bozukluğunun ayrı bir tanı kategorisi olması, bu durumla ilgili farkında-lığı arttıracak, hastaların uygun değerlendirme ve tedavisini sağlayacak, bu alandaki araştırmalara ivme kazandıracaktır. [78] Klinik örneklemlerde deri yolması olan hastalarda trikotillomani ve OKB'nin genel topluma göre; OKB'nin kontrol grubuna göre daha yaygın olması; [1,4,12] OKB hastalarında ve birinci derece yakınlarında deri yolma oranlarının yüksek bulunması [16] bu bozuklukların birbiriyle ilişkili olabileceğini destekler.…”
Section: Tanı öLçütleriunclassified
See 1 more Smart Citation